ANALISIS RESEPSI BUDAYA POPULER KOREA PADA ETERNAL JEWEL DANCE COMMUNITY YOGYAKARTA - Cahya Tunshorin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Korean Popular Culture (K-POP)comes to Indonesia in various mass media. It was aired by entertain programs such as dance, music, series, and fashion. Indonesian audience as active audience produce various meaning of the mass medias programs. That makes so many K-POP fans community was created and adopt the popular culture that given by K-POP. K-POP as new culture comes in the middle of Indonesian culture and that’s also depending to the audience itself. The audience can give various meaning to the K-POP and adopt it to their daily live.This research was aimed to describe audience reception of Korean Popular Culture (K-POP) using reception analysis Stuart Hall’s encoding-decoding.The type of the study was qualitative interpretation. The data obtainable from in-depth interview with the Eternal Jewel Dance Community as informant ofthis research that consistent in K-POP. The informantwas divided into three meaning positions these are Dominant Reading, Negotiated Reading, and Oppositional Reading. The result of this study showed that in some conditions the informant belongs to Negotiated reading and Dominant reading. Age, gender, education, and experience also influence the way informant give the meaning.